A Systematic Literature Study to Unravel Transparency Enabled by Open Government Data: The Window Theory. Issue 3 (3rd May 2020) - Matheus, Ricardo; Janssen, Marijn
Abstract: The opening of data has been credited for improving transparency and for providing a window on government functioning. Although this relationship is intuitively apparent, it is in fact complex and the mere opening of data might not actually yield transparency. In this paper, a comprehensive model of determinants that enable or impede transparency enabled by open government data and the expected effects have been derived by surveying public administration and information systems literature. Public administration literature tends to be focused on factors such as participation and trust, whereas information systems literature focuses on factors such as user interface, user experience, and data quality. Digital government literature attempts to bridge these elements. The Window Theory is introduced, in order to unify existing models by integrating a broad range of factors within a single model. The Window Theory can be used to develop context-dependent models that are both comprehensive and parsimonious.